Disseminating evidence to equine practitioners - Wild, Isabella (2018)
Abdominal pain is a significant welfare concern in equids and is frequently seen as an emergency in first opinion veterinary practice. Although there is a wealth of research into the condition at referral level, there is a paucity of studies with relevance to the primary assessment of the colic case. Furthermore, there is a wide variation on techniques used by veterinary practitioners, most based on anecdotal evidence or clinical experience. This has highlighted the requirement of development of evidence in this area to assist with the primary assessment of the colic case. The aim of the project was to explore methods of disseminating evidence-based materials in equine veterinary practice. There were three phases: Phase 1 assessed methods of dissemination of evidence for practitioners, Phase 2 generated consensus statements on the primary assessment of colic and Phase 3 developed methods of dissemination, based on the outcomes of Phases 1 and 2. The aim of the first phase was to identify barriers to knowledge transfer in equine practice. Semi-structured interviews were conducted with seven equine veterinary practitioners on how they accessed information, barriers they faced, and their preferred options for knowledge transfer (Appendix I). Interviews were recorded, transcribed, and analysed using thematic analysis. Based on these outcomes, an online questionnaire on knowledge transfer in equine practice was developed and distributed. Analysis of the interviews identified three main areas: practitioners’ experience, time constraints and accessibility, with an overarching theme of practice culture. Preferred methods of knowledge transfer included apps and web-based resources, but several practitioners also relied on hard copy resources. The importance of concise, visual information was highlighted. There were 129 participants in the online survey. The main barriers identified were lack of time (76.4% participants) and difficulty accessing articles (65.2%). The resources accessed most frequently on a daily basis were apps (14.3%) and online papers (12.1%), and on a weekly basis were textbooks (29.7%) and online papers (23.1%). The preferred methods of knowledge transfer were websites and online publications (89.2% and 84.3% survey participants likely/very likely to use these). This study was the first step to understanding how information is accessed in practice, and how resources can be developed to maximise uptake.